Standard deviation of individual response for VO2max following exercise interventions: a systematic review and meta-analysis - Renwick, J. R. M.; Preobrazenski, N.; Wu, Z.; Khansari, A.; LeBouedec, M. A.; Nuttall, J. M. G.; Bancroft, K. R.; Simpson-Stairs, N.; Swinton, P. A.; Gurd, B. J. (Sports Medicine, 2024)
Background: Although numerous attempts to demonstrate inter-individual differences in trainability across various outcomes have been unsuccessful, the investigation of maximal oxygen consumption (VO2max) trainability warrants further study. Objective: Our objective was to conduct the first systematic review and meta-analysis to evaluate inter-individual differences in VO2max trainability across aerobic exercise training protocols utilizing non-exercising comparator groups. Methods: We conducted a literature search across three databases: EMBASE, PubMed and SCOPUS. The search strategy incorporated two main concepts: aerobic exercise training and VO2max. Studies were included if they used human participants, employed standardized and supervised exercise training, reported absolute or relative VO2max, included a non-exercise comparator group, reported VO2max change scores for non-exercise and exercise groups and provided the standard deviation (SD) of change for all groups. We calculated the SD of individual response (SDIR) to estimate the presence of inter-individual differences in trainability across all studies. Results: The literature search generated 32,968 studies, 24 of which were included in the final analysis. Our findings indicated that (1) the majority of variation in observed change scores following an intervention is due to measurement error, (2) calculating SDIR within a single study would not yield sufficient accuracy of SDIR due to generally small sample sizes and (3) meta-analysis of across studies does not provide strong evidence for a positive value. Conclusion: Overall, our meta-analysis demonstrated that there is not strong evidence supporting the existence of VO2max trainability across single interventions. As such, it appears unlikely that clinically relevant predictors of VO2max response will be discovered.